Anti-microbial Functions of Group 3 Innate Lymphoid Cells in Gut-Associated Lymphoid Tissues Are Regulated by G-Protein-Coupled Receptor 183 - Chu, Coco; Moriyama, Saya; Li, Zhi; Zhou, Lei; Flamar, Anne-Laure; Klose, Christoph S.N.; Moeller, Jesper B.; Putzel, Gregory G.; Withers, David R.; Sonnenberg, Gregory F.; Artis, David (Cell reports (Cambridge), 2018)
The intestinal tract is constantly exposed to various stimuli. Group 3 innate lymphoid cells (ILC3s) reside in lymphoid organs and in the intestinal tract and are required for immunity to enteric bacterial infection. However, the mechanisms that regulate the ILC3s in vivo remain incompletely defined. Here, we show that GPR183, a chemotactic receptor expressed on murine and human ILC3s, regulates ILC3 migration toward its ligand 7α,25-dihydroxycholesterol (7α,25-OHC) in vitro, and GPR183 deficiency in vivo leads to a disorganized distribution of ILC3s in mesenteric lymph nodes and decreased ILC3 accumulation in the intestine. GPR183 functions intrinsically in ILC3s, and GPR183-deficient mice are more susceptible to enteric bacterial infection. Together, these results reveal a role for the GPR183-7α,25-OHC pathway in regulating the accumulation, distribution, and anti-microbial and tissue-protective functions of ILC3s and define a critical role for this pathway in promoting innate immunity to enteric bacterial infection. [Display omitted] •ILC3s from mouse mesenteric lymph nodes and mouse and human intestine express GPR183•GPR183 and its ligand 7α,25-OHC promote ILC3 migration in vitro•GPR183 and 7α,25-OHC regulate the accumulation and function of ILC3s in vivo•GPR183 is required for ILC3-mediated immunity against enteric bacterial infection Chu et al. demonstrate that GPR183 and its ligand 7α,25-OHC regulate the accumulation, distribution, and anti-microbial and tissue-protective functions of group 3 innate lymphoid cells, thus revealing a critical role for this pathway in promoting innate immunity against enteric bacterial infection.